2008
DOI: 10.1016/j.neuropsychologia.2008.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Role of parietal regions in episodic memory retrieval: The dual attentional processes hypothesis

Abstract: Although parietal cortex is frequently activated during episodic memory retrieval, damage to this region does not markedly impair episodic memory. To account for these and other findings, a new dual attentional processes (DAP) hypothesis is proposed. According to this hypothesis, dorsal parietal cortex (DPC) contributes top-down attentional processes guided by retrieval goals, whereas ventral parietal cortex (VPC) contributes bottom-up attentional processes captured by the retrieval output. Consistent with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
296
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(316 citation statements)
references
References 67 publications
(128 reference statements)
16
296
2
2
Order By: Relevance
“…This is consistent with neuropsychological studies showing that patients with parietal lesions reported ABMs that lacked episodic richness (Berryhill et al, 2007;Davidson et al, 2008). With regard to the role of the parietal cortex in episodic memory, the current findings can be interpreted in light of the dual attentional processes hypothesis (Cabeza, 2008;Ciaramelli et al, 2008), which distinguishes between the role of dorsal and ventral parietal regions. More specifically, it proposes that the dorsal parietal region mediates the allocation of attention controlling episodic retrieval depending on the rememberer"s goal, providing top-down attentional support for strategic retrieval processes.…”
Section: Neuropsychological Predictors Of the Proportion Of Internal supporting
confidence: 91%
“…This is consistent with neuropsychological studies showing that patients with parietal lesions reported ABMs that lacked episodic richness (Berryhill et al, 2007;Davidson et al, 2008). With regard to the role of the parietal cortex in episodic memory, the current findings can be interpreted in light of the dual attentional processes hypothesis (Cabeza, 2008;Ciaramelli et al, 2008), which distinguishes between the role of dorsal and ventral parietal regions. More specifically, it proposes that the dorsal parietal region mediates the allocation of attention controlling episodic retrieval depending on the rememberer"s goal, providing top-down attentional support for strategic retrieval processes.…”
Section: Neuropsychological Predictors Of the Proportion Of Internal supporting
confidence: 91%
“…Third, both patients are deficient in the ability to imagine or construct future events, a memory process that is thought to rely on the retrieval of episodic memories (Berryhill, Picasso, & Olson, submitted). These findings bolster the claims of fMRI studies linking PPC activity to LTM retrieval processes (reviewed in Cabeza, 2008;Wagner, Shannon, Kahn, & Buckner, 2005;Vilberg & Rugg, 2008) while calling into question the dissociation between short-term and long-term memory reported in prior studies of patients with unilateral damage to the parietal lobe (Shallice & Warrington, 1970).…”
Section: Generality Of Findingssupporting
confidence: 73%
“…Regarding the inferior parietal cortex, some authors have suggested that it supports bottomup attention to memory, that is, the capture of attentional resources by relevant memory cues and/or recovered memories (Cabeza, 2008;Cabeza et al, 2008;Ciaramelli et al, 2008).…”
Section: Functional Connectivity During Associative Cermentioning
confidence: 99%